How does environmental heterogeneity affect biodiversity in freshwater ecosystems and how does it vary? - Janaina Uchôa Medeiros Agra (2022)
Environmental heterogeneity (EH) is one of the most investigated environmental factors in freshwater ecosystems around the world. It is expected that more heterogeneous ecosystems harbor greater biodiversity, but negative effects of EH on biodiversity are also observed in nature. Variations in the response of biological communities to the increase in EH are attributed to several factors, raising doubts about its ecological significance. Therefore, I defined the following question for this thesis: How does environmental heterogeneity affect biodiversity in freshwater ecosystems and how can anthropogenic disturbance interfere with the effect? To answer this question, I established two main objectives: 1st) To synthesize the status of knowledge about the relationship between EH and the multiple facets of biodiversity in freshwater ecosystems and estimate the overall effect of EH over multiple facets of biodiversity; 2nd) To investigate the effect of anthropogenic disturbances on the relationship between EH and the multiple facets of the biodiversity of aquatic insects from streams in the Neotropical Savanna. In the first chapter, I systematically reviewed 98 articles and presented a synthesis of EH concepts and methodologies. Also, using a meta-analytical approach, I estimated the overall positive effect of EH over the taxonomic and functional alpha diversity of freshwater communities. The positive effect of EH on alpha taxonomic diversity did not vary between biological communities from temperate and tropical zones, from lentic and lotic ecosystems, or between experiments that controlled the area effect and those that did not. Nonetheless, it was not possible to estimate significant effects of EH over the respective taxonomic and functional beta components of biodiversity. In the second chapter, I demonstrate how the effect of EH varies in aquatic insect assemblages, which were submitted to three different levels of anthropogenic disturbances. Through a model selection approach, I identified EH metrics that have better ecological relevance to explain the increasing taxonomic and functional alpha diversity at each disturbance level, namely: the water flow diversity (in streams least-disturbed) and the variation in channel depth (in streams most-disturbed). As a general conclusion, it is possible to state that EH is a fundamental environmental factor to increase taxonomic and functional alpha diversity in different freshwater ecosystems around the world, but its effect varies depending on the levels of anthropogenic disturbances to which biological communities are submitted.